Artificial Intelligence for Inclusive Learning within Sharia Educational Ethics - Ninda Lutfiani; Kanon Mommsen Wongkar; Tatik Mariyanti; Rifqa Nabila Muti; Noah Rangi (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
The integration of Artificial Intelligence (AI) in education has created new opportunities to enhance inclusive learning across diverse educational contexts. In Islamic educational institutions, the adoption of AI presents a dual responsibility to embrace technological innovation while ensuring alignment with Sharia based ethical principles that emphasize justice, accountability, and respect for human dignity. This study investigates how AI is utilized to support inclusive learning within Islamic education settings in Southeast Asia using a qualitative descriptive approach with a multi-site case study design. Data were collected through semi-structured interviews with teachers, school leaders, and IT developers from selected Islamic educational institutions and analyzed using thematic coding techniques. The findings reveal that AI contributes positively to inclusive learning by enabling adaptive instruction, personalizing learning content, facilitating early identification of learning barriers, and supporting data-driven decision-making. When implemented within Sharia-compliant ethical frameworks, AI enhances fairness, balanced participation, and student engagement. However, the study also identifies several challenges, including limited content filtering mechanisms, insufficient data privacy governance, and the risk of algorithmic bias that may unintentionally marginalize certain student groups. This research highlights the importance of ethical governance and value-based AI design to ensure that AI adoption in Islamic education remains equitable, inclusive, and contextually appropriate. The findings provide strategic implications for institutional policy development, curriculum planning, and the long-term governance of AI-driven educational systems within Islamic educational environments.